Energy ad a criterion for frame discarding and multiplexing efissiency - Shah, Asadullah; Dwi Handayani, Dini Oktarina (IIUM Press, 2011)
To design a STOM on the criterion of energies of each frame is one of the popUlar methods. In this each frames energy is calculated, a frame with lower energy is the best candidates among all users' speech frames. Dropping the frame with lmvest energy may degrade quality at its minimum as compared to the higher energy signals. This is also perceptually less important. Such frames of speech can be utilised to maximize the users on the link. This chapter talks about energy criterion as packet discarding for STDM designs